The effectiveness of soluble protein extractability under the effect of pH, molarity and type of buffers of three different major skeletal muscles in cattle - Sazili, Awis Qurni; M. Z., Noor Azihan; Mustafa, Shuhaimi; Abdullah, Muhammad Hilmi; Panandam, Jothi Malar (Knowledgia Review, Malaysia, 2010)
The present study was conducted in an attempt to study the effects of the type, pH and molarity of extraction buffer on protein extractability from beef Longissimus dorsi (LD), Supraspinatus (SS) and Semitendinosus (ST) muscles. All muscle samples were dissected out from carcass immediately after slaughter and subjected to extractions using freshly prepared buffers of different buffer type (Tris Base and Tris HCl), pH (8.3 and 7.5) and molarity (100 and 20 mM). Following extraction, the total extractable protein concentration was determined by Bradford assay. The results exhibited significant (p<0.05) effects of muscle type X buffer interaction on extracted total protein concentration. The statistical analysis also revealed interaction between type of buffer, pH and molarity significantly (p<0.01), affected the extracted protein concentration. Based on the results, optimal buffer suggested to use for muscle protein extraction is Tris-Base with pH 8.3 and 100 mM. The present study demonstrated that the extractability of skeletal muscle protein was significantly influenced by the type, molarities and pH of the extraction buffers used.